Mesoscale combustor-powered thermoelectric generator with enhanced heat collection. (1st February 2020) - Li, Guoneng; Zhu, Dongya; Zheng, Youqu; Guo, Wenwen
Highlights: A mesoscale combustor-powered TEG was designed and tested. Electric power of 25.7 W was generated with an overall efficiency of 2.69%. Serpentine channels were designed to enhance heat collection from flue gases. The proposed parameter EFS reached 81.8% and it is higher than previous reports. Abstract: Small-scale power sources for portable electronic equipment have been attracting considerable attention in recent years. This paper presents the design and experimental tests of a mesoscale combustor-powered thermoelectric (TE) generator (TEG) with enhanced heat collection. The TE effect, combustion, heat collection efficiencies, and lean blowout (LBO) are investigated in detail. A parameter named system effectiveness (EFS), which is the ratio of overall efficiency to TE efficiency, is proposed to evaluate the performance of combustor-powered TEGs. The obtained electric power of 25.7 W, with an overall efficiency of 2.69%, is higher than previous results. The corresponding hot-end temperature changes from 236 °C to 152 °C along with the flue gas direction, indicating noticeable temperature variation despite the use of pure copper. EFS reaches 81.8%, which is higher than previous reports, and validates that the present TEG is well-designed. The LBO of the combustor is 0.63, and the pressure drop is 463 Pa when the input power is 957 W. Detailed discussions and comparisons with previous studies reveal that the enhanced heat collection design is essential for increasing the residence time of flue gases and EFS.